PELAKSANAAN FUNGSI DPRD KABUPATEN KARANGANYAR - Santosa, Y. Budi (JI@P, 2017)
This study aimed to analyse the role of legislature in drafting local regulations,local budgets and supervision. These efforts are aimed at improving the publicwelfare. Descriptive qualitative research strategy was selected to answer theformulated research problems. Primary as well as secondary data werecollected. Primary data was collected by using interview indepth data collectingtechnique by interviewing some selected relevant informen, most of them werethe members of the legislature at Regency Level in Karanganyar Regency.Research results indicated that: (1) Role of local regulation planning informulating local regulations seemed surprisingly high. It was indicated that in2015 it was targeted that fourteen local regulation should be formulated, butevidently the legislature had already formulated twenty nine local regulations.(2) Research results indicated however, that the function of local legislaturebudget was not implemented efficiently nor effectively. Research result alsoshowed that dealing with budget, the transparancy, accuntability, and timelineshad not fulfilled the justice principles. It was found that the budget wasformulated without using the performance approach. However, at first it waspredicted that the revenue and expenditures of Karanganyar Regency in theyear of 2014 budget was deficit, but in the accountability of the application ofrevenue and expenditures in the year of 2014 was able to be budget surplus.This was the evident that there was collaboration and synergy between thelegislature and the Regency Government of Karanganyar in order to realize thepublic welfare.Key words: regulation; revenue and budget; public welfare; transparancy;accountability; timelines.